From Digital Twin to Memory Twin: A Holistic Framework for Cultural Heritage Documentation, Interpretation, and Adaptive Reuse - Cassar, Anthony; Baker, Drew; Ioannides, Marinos (My University, 2025)
Cultural heritage worldwide is increasingly at risk due to climate change, armed conflict, urbanisation, illicit trafficking, and the broader forces of globalisation. These natural and human-induced threats contribute to the irreversible loss of both tangible and intangible cultural assets. In response, heritage digitisation has advanced significantly - from basic 2D documentation to sophisticated 3D technologies - underscoring the urgent need for structured, ethically grounded methodologies in data acquisition. This paper introduces the Memory Twin: an innovative framework that redefines digital heritage representation by integrating high-fidelity visuals with Paradata, Metadata, Data and intangible cultural values. Building on and extending the Holistic Historic Building Information Modelling (HHBIM) approach, the Memory Twin enriches digital heritage environments with narrative, emotional, and community-driven content, fostering inclusive access, transparency, and long-term cultural significance. Developed within the framework of the EU-funded HERITALISE project, this paper explores both the theoretical foundations and practical application of the Memory Twin through a detailed case study of Villa Portelli in Malta. By integrating 3D scanning, archival research, oral histories, and participatory engagement, the project constructs a multi-dimensional digital portrayal of the site’s material, historical, and social layers. Aligned with the FAIR (Findable, Accessible, Interoperable, Reusable) and CARE (Collective Benefit, Authority to Control, Responsibility, Ethics) principles, the Memory Twin ensures semantic interoperability, ethical stewardship, and community empowerment. It marks a paradigm shift in heritage digitisation - from static documentation toward participatory, value-driven preservation - offering a scalable, sustainable model for safeguarding cultural heritage amid global challenges.
Keywords: Digital Cultural Heritage; Digital Acquisition; EU VIGIE 2020/654; Complexity Analysis; Quality Analysis, Paradata